2015
DOI: 10.1142/s1758825115500520
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Field on Free Convection in Inclined Cylindrical Annulus Containing Molten Potassium

Abstract: Three-dimensional (3D) numerical simulation of natural convection of an electrically conducting fluid under the influence of a magnetic field in an inclined cylindrical annulus has been performed. The inner and outer cylinders are maintained at uniform temperatures and other walls are thermally insulated. The governing equations of this fluid system are solved by a finite volume (FV) code based on SIMPLER solution scheme. Detailed numerical results of heat transfer rate, Lorentz force, temperature and electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 98 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Fe 3 O 4 nanoparticles are magnetite; thus, fluid flow and heat transfer of this nanofluid can be changed by a magnetic field. In many previous studies, the effects of the magnetic field on fluid flow and heat transfer rate have been reported [26][27][28][29][30][31][32]. In this study, for the first time, the composition of functionalized multi-walled carbon nanotubes (f-MWCNTs) and iron oxide (Fe 3 O 4 ) nanoparticles is dispersed in ethylene glycol (EG) as a base fluid.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 92%
“…Fe 3 O 4 nanoparticles are magnetite; thus, fluid flow and heat transfer of this nanofluid can be changed by a magnetic field. In many previous studies, the effects of the magnetic field on fluid flow and heat transfer rate have been reported [26][27][28][29][30][31][32]. In this study, for the first time, the composition of functionalized multi-walled carbon nanotubes (f-MWCNTs) and iron oxide (Fe 3 O 4 ) nanoparticles is dispersed in ethylene glycol (EG) as a base fluid.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 92%
“…Their results revealed that the effect of transverse magnetic field on the average Nusselt number is more effective than that of the axial magnetic field. Further, Afrand et al [25] performed 3D numerical simulation of natural convection of molten potassium in an inclined cylindrical annulus exposed to a magnetic field. They reported that a magnetic field can control the natural convection of molten potassium.…”
Section: Introductionmentioning
confidence: 99%
“…(16), we have: (18) A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 8 Then the specified length is obtained equal to . By balancing the heat transfer at the inner boundary, is obtained as follows:…”
Section: -B )mentioning
confidence: 99%
“…The convective heat transfer between two cylinders has attracted considerable attention due to its wide applications such as finding the methods in order to improve the crystals formation, food production, microchannels, pipes and bearings [1][2][3][4][5][6][7][8]. Although many progresses have been carried out to improve the heat transfer enhancement, by progressing the equipment and their becoming small in size, it seems that the more heat transfer in the less space is necessary.…”
Section: Introductionmentioning
confidence: 99%